PERNIKAHAN BEDA KEWARGANEGARAAN STUDI ANALISIS HUKUM ISLAM DAN HUKUM POSITIF - Jamilah, Fitrotin (Program Pascasarjana Universitas Sunan Giri Surabaya, 2018)
Marriage is an inner bond between a man and woman as husband and wife  with the aim of forming a happy and eternal family or household based on the supreme devinity, indonesia has many practices of marriage including mixed marriages, different religions and different nationalities, and the goals of this study, 1) marriage in islamic law,2) marriage in law no.1 of 1974, 3) marriage in the kuhperdata bw, 4) marriage  interfering with different natonalities in islamic law and phosphorus law